Design of Stack Foundation in Berau Coal Steam Fire Power Plant on Soft Silty Clay Embankment - Widayat Amariansah (International Conference on Coastal and Delta Areas, 2015)
Berau CSFPP 2x7 MW is under construction now in Berau river estuary in NorthKalimantan province. This power plant has steel structure stack of 40 m height with 3028 mm diameter. Stack foundation is standing on soil embankment of 3,30 m height above original soil to anticipate tidal river water level and to have plain level in power plant areas. Below the embankment, original soil are consist of very soft-soft silty clay in 1-14 m depth with N-SPT = 1-2, qc = 1-21 kg/cm2; soft-medium stiff clayey silt in 14-23 m depth with N-SPT = 3-15, qc = 22-38 kg/cm2 and very stiff-hard silty clay in 24-30 m depth with N-SPT = 16-23, qc = 39-47 kg/cm2. Based on this condition, stack foundation has been designed with 25 points concrete pile K.600, Ã˜ = 400 mm and 30m length. Design loads are consist of deadly weight stack, pile cap, concrete pile; wind load at top of stack in 120 km/hours velocity; earthquake; impact load and uplift force due electromechanical vibration; extended moment due eccentricity and negative skin friction. Pile stabilization calculationare satisfied enough i.e. bearing capacity ratio 1,63; safety factor for block failure 1,03 and uplift 8,47; settlement 3,25 cm.